Detection of CCR5Δ32 Mutant Alleles in Heterogeneous Cell Mixtures Using Droplet Digital PCR - Sorokina, Alyona; Artyuhov, Alexander; Goltsova, Alexandra; Dashinimaev, Erdem (Frontiers in Molecular Biosciences, 2022)
The C-C chemokine receptor type 5 (CCR5 or CD195) is one of the co-receptor binding sites of the human immunodeficiency virus (HIV). Transplantations of hematopoietic stem cells with the CCR5Δ32 knockout mutation could represent an effective tool for the complete cure of HIV; these methods have passed the stage of proof-of-principle. At the same time, using the modern CRISPR/Cas9 genome editing method, we can effectively reproduce the CCR5Δ32 mutation in any wild-type cells. Thus, the task of searching for and accurately quantifying the content of mutant CCR5Δ32 alleles in heterogeneous cell mixtures becomes relevant. In this study, we describe the generation of an artificial CCR5Δ32 mutation using CRISPR/Cas9 followed by multiplex droplet digital polymerase chain reaction (ddPCR) to quantify its content in cell mixtures. The system we have developed allows us to quickly and accurately measure the content of cells with the CCR5Δ32 mutation, down to 0.8%.